Outdoor physical education in French schools during the twentieth century. Issue 2 (3rd April 2017) - Attali, Michaël; Saint-Martin, Jean
ABSTRACT: During the twentieth century, outdoor physical education (OPE) gradually integrated with the French education system. Culturally speaking, OPE had to overcome several hurdles because it promoted values such as freedom, initiative and responsibility that were deemed incompatible with the existing educational model. Beyond being a pedagogical tool, the health and welfare implications justified the existence of OPE within the school system, thus changing the meaning of those values. The question of human relations with nature truly facilitated the incorporation of OPE into French educational programmes even if the scope of its development is rather limited today. Some might regret the predominance of a kind of physical activity that conveyed values and was proven to be especially productive in terms of issues related to education, security and respect for the environment. Nevertheless, OPE physical activities found their rightful place within the school system because of the sports facet of the activities.